Composite processed by RTM: Fatigue behavior - Cioffi, Maria [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Shiino, Marcos Yutaka [UNESP]; Rezende, Mirabel Cerqueira (My University, 2011)
Structural polymer composites have been widely applied in the aeronautical field. However, composite processing, which uses unlocked molds, should be avoided in view of the tight requirements in service and also due to the possibility of environmental contamination. To produce composite aeronautical structural components with low cost, the aircraft industry has shown interest in resin transfer molding process (RTM) as an adequate option to substitute for conventional process with the advantages of faster gel and cure times, besides the low percentage of voids and high fiber volume percentage, which are the essential parameters to design aircraft structures. Since the low viscosity resin is injected into the closed mold, in this process, the edge effect can promote incomplete wetting of the fiber reinforcement, dry spot formation and other defects in the final composite. Knowledge of material behavior is essential to design structures as aircraft landing gear, for example. Compared with isotropic materials, polymeric fibrous composites submitted to cyclic loading present a degradation phenomenon of mechanical properties as a consequence of residual stress redistribution into the structure. It was established that fatigue mechanisms associated to fibrous composites occur in four stages: nucleation of local damage, stable propagation of crack due to the cyclic load, local crack propagation which is dependent of fibers orientation, the matrix ductility and the interfacial adhesion and propagation of last loading cycle, which is analogous to the tensile test fail. Because of the many mechanisms involved during the degradation of the composites, scatter in fatigue is higher and special care need to be taken when approach the S-N curve. In this chapter, the review of data presented in the literature with focus in the fatigue behavior of polymeric composites reinforced with carbon fiber processed by RTM are compared with some experimental data obtained during three years of study. As a specific aim this chapter proposes a new methodology for fatigue behavior on composites, as this field lack of reliable predictive methods, and the main drawbacks of composites applied in aircraft structures.